The everything pregnancy book : all you need to get you through the most important nine months of your life! - Ford-Martin, Paula; Aron, Elisabeth A. (Avon, Mass. : Adams Media, 2007)
Looks at the physical and emotional changes during pregnancy, discussing changes of both mother and baby month-by-month, and describes medical procedures, exercise, diet, and breast feeding.
Includes index.
'Completely updated'--Cover.
Keywords: Pregnancy -- Popular works; Childbirth -- Popular works